OPTICAL PROPERTIES OF LIQUID CRYSTALS AND THEIR LASING SPECTRA - Ільчишин, І.П.; Липницький, С.О. (Science-based technologies, 2009)
Influence of thickness of active layer and value of double refraction on position of lasing spectra of the distri-buted feed-back (DFB) laser based on cholesteric liquid crystals (CLC) was studied. Is explored, that its spec-trum in steroidal CLC, unlike of induced CLC, is placed within the limits of selective reflection (SR) band and practically small depend on a thickness and optical quality of layer. For doped induced CLC with large double refraction the lasing spectra are always placed on edge of the SR band. The conducted researches showed that the lasing in doped steroidal CLC, unlike of induced CLC, to describe the model of coupled waves.